Extrinsic and idiopathic vernal keratoconjunctivitis? Two cases with dissimilar immunopathology. Issue 11 (November 1983) - Zavaro, A; Baryishak, Y R; Samra, Z; Sompolinsky, D
Abstract : Two clinically similar cases of vernal keratoconjunctivitis with dissimilar immunological data are reported. One patient had strikingly elevated IgE levels in both serum and tears, and his tear fluid contained specific IgE antibodies to a number of allergens. Conjunctival scrapings and peripheral blood samples showed marked eosinophilic reactions. The other patient showed normal values for tear and serum IgE; no IgE type antibodies to allergens were detected; and no local or systemic eosinophilic reactions were observed. The immunopathogenesis of these cases is discussed.